EFEK AFRODISIAKA DARI PERBEDAAN WAKTU PEMBERIAN SEDIAAN INFUSA CAMPURAN AKAR PURWOCENG (Pimpinella pruatjan Molkenb.), RIMPANG JAHE MERAH (Zingiber officinale Rosc.), DAN BUAH CABE JAWA (Piper retrofractum Vahl.) TERHADAP TIKUS PUTIH JANTAN - Budiawan, Antonius (Widya Warta, 2020)
Purwoceng (Pimpinella pruatjan Molkenb.), red ginger (Zingiber officinale Rosc.), and javanese long pepper (Piper retrofractum Vahl.) have been investigated for their aphrodisiac properties. This study aimed to determine the time of administration and duration of purwoceng root, javanese long pepper fruit, and red ginger rhizome mixture infusion that provide the highest aphrodisiac effect. Twenty five males of Wistar strain white rats were divided into five groups consisting of five rats. Group I: positive control(PASAKBUWONOCENGÂ®), group II: negative control (water), group III: 1-time dose dosage(2.4grams) in the morning, group IV: 1-time dose dosage (2,4grams) in the afternoon, and group V: half dose dosage (1,2grams) in the morning and a half dose dosage (1,2grams) in the afternoon. The study was conducted for seven days. The infusion preparation was given every day for five days, starting on the second day of the study. The rats' climbing frequencies were observed and recorded on the day 0, 2, 4, and 6. The results showed that the purwoceng (Pimpinella pruatjan Molkenb.), red ginger rhizome (Zingiber officinale Rosc.), and javanese long pepper (Piper retrofractum Vahl.) mixture infusion had the aphrodisiac effect. One dose dosage (2,4grams) in the afternoon of infusion showed the highest aphrodisiac effect. The length of the day of infusion that showed the highest aphrodisiac effect was the fourth day.